Ocupações com indicação de tecnologia assistiva em crianças com Transtorno do Espectro Autista por terapeutas ocupacionais - Ferreira, Kétlin Cristina (2025)
Children with Autism Spectrum Disorder (ASD) often have their occupations affected by issues related to delayed development of performance components and changes in sensory processing. Despite the current broad discussion on intervention strategies and approaches with this population, little emphasis is placed on the indication and use of Assistive Technology (AT) as an important intervention resource to promote the participation and engagement of children with ASD in occupations. In this sense, this research aims to contribute to the production of knowledge in the area, starting from the perspective of occupational therapists. Objective: To map the resources, strategies and devices of Assistive Technology indicated by occupational therapists in the occupations of children with Autism Spectrum Disorder. Methodology: This is an exploratory, descriptive study with quantitative and qualitative approaches, which began with the construction of a specific questionnaire, approved by evaluators with experience in the area, aimed at occupational therapists. Quantitative data were analyzed using descriptive statistics and qualitative data were analyzed using content analysis, data categorization and visual maps. Results: After extensive dissemination, 37 occupational therapists who work with children with ASD in 11 Brazilian states participated, providing services in private offices or clinics (67.6%) and the other 32.4% distributed in Associations of Parents and Friends of Exceptional Children (APAEs), Specialized Rehabilitation Centers (CERs), Non-Governmental Organizations (NGOs), as well as Associations and centers related to ASD and Regular Schools. It was possible to identify that there are AT resources, devices and strategies that can be used within children's occupations: play, social participation, education and activities of daily living (feeding, bathing, personal/sanitary hygiene, dressing and undressing) of children with ASD, such as the use of visual cues, communication resources and changes in the strategy for carrying out the activity. The results showed that although all occupations presented indications for the use of AT, education and ADL personal hygiene/sanitary activities stood out with the highest number of indications. In the activity of personal hygiene, visual cues stood out, in play the use of offers and strategies for self-regulation was the most selected, in education, adaptations and/or making adapted materials was the most indicated. The category of assistive technology most mentioned by the participants was “aids for daily living and practical life” with 97.3% and the category of augmentative and alternative communication with 83.8%. Although occupational therapists consider it important for clinical practice and in children's occupations, the search for references for assistive technology is little compared to its importance and the indication of AT has been presented more with the term resources and adaptations rather than assistive technology itself. Final considerations: Assistive technology is among the different intervention strategies that can be adopted with children with ASD and were associated with different children's occupations, with emphasis on Education, which had all assistive devices selected by more than half of the participants, as well as the ADLs that were presented with emphasis on specific needs for indication for each of them.